Contribution of Adversity Quotient, Anxiety, and Achievement Motivation toward Students’ Speaking Competency - Wirayadnya, I Ketut (Universitas Pendidikan Ganesha, 2012)
The aim of this study was to investigate the contribution of adversity quotient, anxiety, and achievement motivation towards students’ speaking competency. The study involved three independent variables namely adversity quotient, anxiety, and achievement motivation and one dependent variable namely students’ speaking competency. The design of this research was a correlational research with regression technique. The population was 146 students and the size of the sample was determined by using Kretjie and Morgan formulas. The findings revealed that the contribution of adversity quotient towards students’ speaking competency was 6.94% while anxiety contributed to students’ speaking competency by 26.90% and 33.71% for the contribution of achievement motivation towards students’ speaking competency. The total contribution of the three independent variables towards the dependent variable was 67.55%. The degree of contribution proved that adversity quotient, anxiety, and achievement motivation contributed positively to the speaking competency of students of English Education Department.